Objective assessment criteria reduce the influence of judgmental bias on grading - Peter, Sophia; Karst, Karina; Bonefeld, Meike (Frontiers in Education, 2024)
Past research has indicated that students with a migration background are graded worse than those without a migration background, despite them showing the same level of academic performance.Negative implicit associations of teachers associated with these student characteristics could explain these findings. Objective assessment criteria, such as error tables, provide user-independent rules for the interpretation of results and could therefore help to ensure that the influence of student characteristics on assessment is reduced. To test this hypothesis, 157 pre-service teachers assessed a dictation. Two aspects were varied: the presentation of an error table for assessment and the name of the student who had written the dictation (with vs. without a supposed Turkish migration background). An implicit association test measured implicit associations of the pre-service teachers towards the performance of Turkish and German people. When no error table was used and the preservice teachers had negative implicit associations towards the performance of people with a Turkish migration background, they graded students with a migration background worse than students without a migration background. No grading disparities were found when the error table was used. To reduce judgmental bias, the use of objective assessment criteria can therefore be recommended.